Analisis Indeks Kekeringan Menggunakan Standardized Precipitation Index (SPI) Method pada Daerah Kabupaten Timor Tengah Selatan - Willybrordus Kurniawan Hima; I Made Udiana; Judi K. Nasjono (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2022)
Due to the low rainfall, it is relatively uneven in each sub-district in Timor Tengah Selatan (TTS) Regency. It causes some rivers to be drought-prone in the dry season. This study aims to determine the largest drought index and map the drought distribution in the South Central Timor (TTS) Regency. The drought index analysis uses the Standardized Precipitation Index (SPI) Method. The data used is monthly rainfall data for ten years (2009-2018) of ten rain stations. Then, mapping of drought distribution rainfall using ArcGIS Software. The results of the drought index analysis showed that in the 1-month deficit period, the largest drought index was -3.61, which occurred in March 2014 at the Oeekam Rain Station. In the 3-month deficit period, the largest drought index was -3.19, which occurred in March 2010 at the Nulle Rain Station and in November 2015 at the Kesetnana Rain Station. The findings of the drought distribution map study suggest that during the 1-month shortfall period, all sub-districts experienced drought in January, February, and April. Meanwhile, in the 3-month deficit period, drought occurs evenly for all sub-districts only in June.